The global burden of neglected zoonotic diseases: Current state of evidence - Bari, C. di; Venkateswaran, N.; Fastl, C.; Gabriël, S.; Grace, Delia; Havelaar, A.H.; Huntington, B.; Patterson, G.T.; Rushton, J.; Speybroeck, N.; Torgerson, Paul R.; Pigott, D.M.; et al. (Elsevier, 2023)
The majority of emerging infectious diseases are zoonoses, most of which are classified as “neglected”. By affecting both humans and animals, zoonoses pose a dual burden. The disability-adjusted life year (DALY) metric quantifies human health burden since it combines mortality and morbidity. This review aims to describe and analyze the current state of evidence on neglected zoonotic diseases (NZDs) burden and start a discussion on the current understanding of the global burden of NZDs.